Ten Commandments for Sustainable, Safe, and W/Healthy Sandy Coasts Facing Global Change - Silva, Rodolfo; Oumeraci, Hocine; Martínez, M. Luisa; Chávez, Valeria; Lithgow, Debora; van Tussenbroek, Brigitta I.; van Rijswick, Helena F. M. W.; Bouma, Tjeerd J. (Frontiers in Marine Science, 2021)
Sandy coasts represent about one-third of the global coastline and are among the most valuable and most vulnerable areas for humans and many other species. Socio-economic development and climate change impacts, together with traditional engineering for shore protection, have pervasively resulted in coastal squeeze, thereby threatening coastal life and economic activities, and the very survival of coastal ecosystems. In the past, the responses to problems such as land loss, coastal erosion and flooding were primarily reactive, through grey engineering solutions, with little interest shown in the ecosystem processes impacted by coastal armouring. In recent decades, coastal management strategies have become more diverse, embracing traditional engineering solutions alongside ecosystem-based measures. Even so, many of these new strategies still fail to meet sustainability criteria. Inspired by Per Bruun´s “The Ten Demands for Coastal Protection” from 1972, this paper attempts to consider these changes and knowledge acquired since the 1970s, in order to tentatively formulate “Ten Commandments” for the sustainability of sandy coasts in face of climate change and socio-economic development. As such, the paper offers a new vision and briefly summarizes good practices for the management of sandy coasts, particularly useful for those who, at whatever level of influence, could contribute to the long-term realization of this new vision.